Shedding light on the effects of conflict management training: A multi-rater assessment shines a spotlight on medical students’ skills - Fatemeh Mohseni; Aeen Mohammadi; Nasim Khajavirad; Kamal Basiri; Larry Gruppen; Mahboobeh Khabaz Mafinejad (PLoS ONE, 2025)
Background Medical students are repeatedly exposed to challenging situations while working with healthcare teams, so acquiring conflict management skills is necessary. This study aimed to investigate the effect of an educational intervention on the conflict management skills of medical students using self- and observer-assessment. Methods This educational intervention with a pre-and post-test design was conducted in 2022–2023. Second-year medical students of Tehran University of Medical Sciences volunteered to participate in a randomized study with a control group. The participants were divided into two intervention (12 groups of 4 each, n = 48) and control groups (12 groups of 4 each, n = 48). The intervention group was educated based on the Fogg model, and the control group was trained using conventional method. Student conflict management skills were evaluated using a self-assessment checklist and observer-assessment. Results The findings of observer-assessment revealed that the post-test rating in the intervention group was significantly higher than the control group, while the pre-test score in the two groups did not indicate a significant difference (P = 0.03; ES = 0.44 and P = 0.30; ES = 0.18, respectively). Moreover, the comparison between pre-test and post-test in the two intervention and control groups also showed that the educational intervention significantly increased the mean score of the post-test in both the intervention and control groups (P ≤ 0.001; ES = 0.97 and P ≤ 0.001; ES = 1.34, respectively). The comparison between pre-test and post-test in the two intervention and control groups via self-assessment showed that the skill score increased only in the intervention group (P = 0.02; ES = 0.48 and P = 0.98; ES = 0.004, respectively). Conclusion This study found that using the Fogg model in e-learning platforms enhances medical students’ conflict management skills, highlighting the effectiveness of well-designed, creative, and active model-based teaching methods.